Analyzing Research Trends in Official Development Assistance - Choi, Young-Chool (International Journal of Psychosocial Rehabilitation, 2020)
This study has a twofold purpose: firstly, to analyze the network structure of the co-authors of researchers who have conducted ODA research; and secondly, to find out how the group of core research topics covered in the ODA research field is formed. These purposes are important, because analyzing the characteristics of the co-author’s network structure can provide information about the co-author’s direction of information exchange and about the degree of activation of the information exchange. In ODA research, it is important to understand what keywords are, and which research topics are organized into key groups. As a result of the analysis, it can be seen that the co-author types of researchers who study ODA have many circle types, but relatively few star and Y types. This shows that there is a possibility that an error may occur in information exchange between co-authors, and therefore it is necessary in the future to expand the base of authors who are conducting ODA research. In addition to the above, in terms of key research topics seven research subject groups were drawn. In the future, academic reflection on this field should be continued, and new core concepts need to be studied.